The Use of The Sectorial Coordinate Approach to Demonstrate Unique Shear Centre Properties of Nonstandard Monosymmetric Steel Sections - Muukua, Mervin Mbakekua (Department of Civil Engineering, 2021)
The study looks at how the sectorial coordinate approach can be used to solve the problem of unique shear centre property of non-standard monosymmetric sections. In solving the unique shear centres, the behaviour of the shear centre with reference to the centroid is carefully studied as the geometry of the section is changed. The study shows investigations of the sections which are 152x152x30 UC H-section, the same H-section with 2/3 as well as 1/3 of the bottom flange width and a 203x178x30 T-section. Vertical plates of 8mm thickness are added to the ends of the upper flanges of the sections instigating increments of 12.5mm from 0 to 100mm height. From the computations done, the following is observed: • The difference between the sectorial coordinate approach results and those from Prokon is at most 3.1%. Also, as the end plate heights are increased, the difference in the results increases. • Shear centres change in position with reference to the centroids as a result of the change in geometry of the sections. • For the H-section the shear centre is initially with the centroid at zero plate height. It then moves upward (higher than the centroid) to a certain peak point, then decreases steadily, intersecting the centroid again and eventually ending up being lower than the centroid with upstanding plate height increases. • A similar pattern follows the H-sections with reduced bottom flange widths, with the only difference being that the shear centre is initially higher than the centroid. It slightly increases to a peak then gradually decreases, intersecting the centroid at a certain point and ending up lower than the centroid. • As for the T-section, the shear centre is initially at the highest point (furthest from the centroid) and decreases gradually, intersecting the centroid and ending up lower than the centroid. • The H-section with upstanding plates offers itself as a section that has an envelope (gap) between the shear centre and centroid when the shear centre is above the centroid which is much lesser than the other sections. With the usage of excel spreadsheets, the sectorial coordinate approach is an efficient and accurate method to find shear centres and related section properties.